2022
DOI: 10.1007/s00005-022-00667-4
|View full text |Cite
|
Sign up to set email alerts
|

An Assessment of the Serum Activity of ADH and ALDH in Patients with Primary Biliary Cholangitis

Abstract: Primary biliary cholangitis (PBC; previously known as primary biliary cirrhosis) is a chronic inflammation-induced cholestatic process in the liver. Antimitochondrial antibodies (AMAs) are observed in around 90% of patients, which suggests that PBC is an autoimmune disease. Alcohol dehydrogenase (ADH), ADH isoenzymes and aldehyde dehydrogenase (ALDH) are localized in the liver, and they are useful markers of liver dysfunction. In this study, the activity of total ADH, ADH isoenzymes and ALDH was evaluated in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…ADH catalyzes the oxidation of primary and secondary alcohols to produce corresponding aldehydes and ketones [ 6 ], in which the cofactor nicotinamide adenine dinucleotide (NAD + ) is reduced to NADH [ 7 ]. Studies have reported that in alcoholism or cirrhosis, ADH activity is significantly increased in serum [ 8 , 9 ]. The initial activity of ADH is positively correlated with liver damage-related indicators [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…ADH catalyzes the oxidation of primary and secondary alcohols to produce corresponding aldehydes and ketones [ 6 ], in which the cofactor nicotinamide adenine dinucleotide (NAD + ) is reduced to NADH [ 7 ]. Studies have reported that in alcoholism or cirrhosis, ADH activity is significantly increased in serum [ 8 , 9 ]. The initial activity of ADH is positively correlated with liver damage-related indicators [ 10 ].…”
Section: Introductionmentioning
confidence: 99%